1990
DOI: 10.1084/jem.172.5.1425
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia in transgenic mice expressing interleukin 5.

Abstract: Experiments in vitro suggest that although interleukin 5 (IL-5) stimulates the late stages of eosinophil differentiation, other cytokines are required for the generation of eosinophil progenitor cells. In this study transgenic mice constitutively expressing the IL-5 gene were established using a genomic fragment of the IL-5 gene coupled to the dominant control region from the gene encoding human CD2. Four independent eosinophilic transgenic lines have thus far been established, two of which with 8 and 49 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
328
3
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 548 publications
(350 citation statements)
references
References 19 publications
12
328
3
7
Order By: Relevance
“…IL-5 is a major growth factor for eosinophils and is important for eosinophil expansion in the lung during allergic airway disease (60,61). Overexpression of IL-5 in T cells or in the lung can promote lung eosinophilia (62,63). Since we did not observe decreased IL-5 levels in dnNFAT Tg mice and inhibition of NFAT did not affect IL-5 production by Th2 cells in vitro, this could explain why at late stages of allergic airway inflammation the accumulation of eosinophils in the lung is less affected.…”
Section: Discussionmentioning
confidence: 99%
“…IL-5 is a major growth factor for eosinophils and is important for eosinophil expansion in the lung during allergic airway disease (60,61). Overexpression of IL-5 in T cells or in the lung can promote lung eosinophilia (62,63). Since we did not observe decreased IL-5 levels in dnNFAT Tg mice and inhibition of NFAT did not affect IL-5 production by Th2 cells in vitro, this could explain why at late stages of allergic airway inflammation the accumulation of eosinophils in the lung is less affected.…”
Section: Discussionmentioning
confidence: 99%
“…AAMs in gonadal adipose tissue (GAT) are maintained by IL-4 and/or IL-13 [3]. The activation of eosinophils critically depends on IL-5: studies using il5-tg mice or il5-deficient mice and anti-IL-5 Ab have demonstrated that the expansion of eosinophils is largely regulated by IL-5 [4][5][6][7][8]. Il5-deficient mice show higher body weight and visceral adipose weight in response to a highfat diet [2].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the transgenic construct, IL-5 overexpression has been shown to cause moderate (28) to massive eosinophilia, lower bowel inflammation, and enhanced autoantibody production (29,30). In the present study, two of these IL-5 transgenic mouse lines were utilized.…”
mentioning
confidence: 99%